Impostor syndrome in hospitalists- a cross-sectional study - Susmita Paladugu; Tom Wasser; Anthony Donato (Greater Baltimore Medical Center, 2021)
Impostor syndrome (IS) is a psychological phenomenon in which highly successful people are plagued with self-doubt. Its prevalence in hospitalists and effects of mentoring programs are unknown. We surveyed 71 hospitalists at one hospital for symptoms of IS using the Clance Impostor Phenomenon Scale (CIPS). Mean CIPS score was 53.82 (±17.1). Twenty-four participants (33.8%) had IP scores >60, indicating impostor syndrome. There was no difference in score for men and women (56.70 versus 53.02, p = 0.35). Non-white hospitalists had lower rates of impostor syndrome compared to white hospitalists (25% versus 43%, p = 0.002). Impostors had no difference in years as a hospitalist compared to non-impostors (6.96 versus 6.62 years, p = 0.81). Hospitalists with mentors compared to those without had no difference in rates of impostor syndrome (40% versus 34.1%, p = 0.88). The prevalence of impostor syndrome is similar in hospitalists to other professions. A voluntary mentoring program was not associated with lower prevalence.